Figurative Meaning Used by Chairil Anwar on his Poetry ‘Krawang-Bekasi’ - Dhiana Fadjarwati (JournEEL, 2019)
The purpose of this study was to describe the figurative meaning applied in the poetry written by Chairil Anwar “Krawang-Bekasi”. This study was done by applying descriptive qualitative design by in the semantics theory supported by theory of figurative meaning proposed by Leech (1981). The instrument was the researcher as the primary instrument of the study. The data were examined into the description form within the poetry. The findings showed: (1) This poetry portrayed the war in Military Aggression I and II in Indonesia and described the story of the young soldiers Indonesia to grab Indonesia‘s independency; (2) Chairil Anwar also wrote the peace messages from the young dead soldiers who killed during the war. Chairil Anwar used alliteration and refrain to make a lyrical sound; used visual imagery, internal sensation imagery, and auditory imagery to involve the reader into the poetry. To broaden the reader‘s imaginations, used personification and symbol in case to illustrate the figurative meaning in the poetry.